Iconography’s development for a seniors’ iTV informative platform - Silva, Telmo (2017)
Technological solutions, namely interactive television (iTV) applications, have a lot of potential to deliver adapted solutions to wider audiences or to specific groups of users. Elderly can be one of these groups but require a special attention by specialists due to their specificities. One of the central questions to develop pleasant and usable technological solutions is the iconography used in the applications, as graphical interface elements. To make icons appealing and perceptible visual representations, with a high degree of iconicity ensured, it is important to design them taking end users’ inputs into account. This paper reports on the iconographic design process and its results, carried out in the scope of an academic project that aims to develop an iTV platform for seniors. The purpose of the icons is to support users to perceive, visually, the area in which the information sent through this platform belongs to. After developing three icon proposals per each one of the seven areas of information, the proposals were presented to a group of 19 elderly people who, through election voting test, defined their preferred options. In this work it was also possible to validate a process that can be applied to similar studies. © 2017 The Authors. Published by Elsevier B.V. Peer-review under responsibility of the scientific committee of the CENTERIS - International Conference on ENTERprise Information Systems / ProjMAN - International Conference on Project MANagement / HCist - International Conference on Health and Social Care Information Systems and Technologies.